Garden of secrets past [large type] : an English garden mystery - Eglin, Anthony (Thorndike Press large print mystery, 2011)
Codebreakers have tried for centuries to decipher the inscription on a monument in the garden at Sturminster Hall. When a murder occurs on the garden grounds, the intellectual puzzle becomes all too real, and Dr. Lawrence Kingston - retired professor of botany and reluctant sleuth - is called in to investigate. Convinced that the crime must be linked to the code, Kingston begins hunting for clues and is swept into the undertow of a centuries-old family conflict ...